Analysis of the Integration of Tahfiz Al-Qur'an in the Curriculum: Its Impact on Student Achievement - Effendi, Ahmad; Hairunnisa, Hairunnisa; Jamaliah, Jamaliah (At-tadzkir: Islamic Education Journal, 2025)
This study aims to analyze the integration of the Tahfiz Al-Qur'an program in the education curriculum and its impact on student achievement through a library research approach. This study was conducted by tracing various literature sources such as books, scientific journals, educational articles, and relevant previous research results. The main focus of the study is to understand the concept of tahfiz integration in the general school curriculum and examine its contribution to the cognitive, affective, and spiritual aspects of students. The results of the study indicate that the integration of the tahfiz Al-Qur'an program not only improves students' memorization abilities, but also plays a role in forming disciplined character, strengthening learning motivation, and improving overall academic achievement. This approach has a positive influence on the balance between intellectual and spiritual education, and creates a more religious and conducive learning environment. This study recommends the need to develop an integrative curriculum that combines Al-Qur'an education with general learning systematically, in order to create a holistic and sustainable quality of education.